(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2017)
Many commentaries have been written about the various facets of Kafka’s The Metamorphosis. This paper is an attempt to further examine the deeper aspects of this perennial work, which reveals much about the enormity and the difficulties of embracing one’s self amidst a world that prefers defining labels that wash away any semblance of uniqueness and individuality.